2019
DOI: 10.1161/strokeaha.119.027177
|View full text |Cite
|
Sign up to set email alerts
|

Refined Sphenopalatine Ganglion Stimulator Placement and Intensity Setting to Augment Blood Flow and Neurologic Function

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The 49 patients that received stimulation demonstrated a median NIHSS improvement of 75% compared to 50% in the historical control. Stimulation was also shown to significantly increase CBF and hand motor function within the cohort, but was not compared to the historical control ( 63 ).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The 49 patients that received stimulation demonstrated a median NIHSS improvement of 75% compared to 50% in the historical control. Stimulation was also shown to significantly increase CBF and hand motor function within the cohort, but was not compared to the historical control ( 63 ).…”
Section: Resultsmentioning
confidence: 96%
“…The ImpACT24M study, reported by Saver et al ( 63 ), was a single-arm study assessing the effect of two changes to the SPG stimulation procedure required for implanting and optimizing the device. Primary outcomes were difference in 7-day NIH Stroke Scale (NIHSS), and proportion of patients with improvement in stroke symptoms, compared to historical controls ( 65 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of action in these diseases is blockade of the trigeminovascular network of which the SPG is a component and, more precisely, blockade of the parasympathetic autonomic vasomotor system that is responsible, among other things, for nasal congestion [ 12 ]. In contrast, in stroke, SPG neuromodulation by implanted stimulation targets a stimulant effect on the parasympathetic nervous system [ 36 ] with a demonstrated benefit in terms of increased cerebral blood flow secondary to the release of vasodilator neurotransmitters (Nitric Oxide, acetylcholine), decreased cerebral oedema due to stabilisation of the blood-brain barrier, and potentially a neuroprotective effect [ 37 ]. In particular, it should be noted that high-frequency implanted SPG stimulation induces a reduction of postganglionic parasympathetic activity [ 13 ], while a parasympathetic stimulant effect is observed in response to low-frequency stimulation, with the consequent risk of cluster-like attacks [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hand pinch and grasp strength improved in parallel with degree of cervico-cranial blood flow improvement. 30 Indirect evidence suggests that CBF increase via collateral enhancement also contributed to the 3 m global disability benefit of SPG-Stim observed in the combined ImpACT-24A and ImpACT-24B trials. SPG-Stim benefit was confined to the confirmed cortical infarct (CCI) population, who had features at entry that would predispose to greater benefit from CBF enhancement, including: (1) NIHSS 10, selecting for patients with persisting large vessel occlusion who are more likely to have penumbral tissue still present beyond 6 h post-onset; and (2) hypodensity in one or more cortical regions, selecting for patients with superficial strokes in whom leptomeningeal collaterals play a more important role in vascular supply.…”
Section: Mechanisms Of Action Of Spg Stimulation (Figure 3)mentioning
confidence: 99%